The Oxford handbook of prisons and imprisonment - Wooldredge, John; Smith, Paula (The Oxford handbooks in criminology and criminal justice, 2018)
The imprisonment boom of the late 20th century : past, present, and future / Mona Lynch and Anjuli Verma -- Who goes to prison? / Daniel P. Mears and Joshua C. Cochran -- Mass incarceration and conditions of confinement / Leo Carroll, Sharon Calci, and Amber Wilson -- Exploring imprisonment across cross-national contexts / Paul Mazerolle, John Rynne, and Samara McPhedran -- Theories of mass incarceration / Natasha A. Frost and Todd R. Clear -- Subcultural adaptations to incarceration / Ben Crewe and Ben Laws -- The real gangbanging is in prison / Scott H. Decker and David Pyrooz -- Women in prison / Emily M. Wright and Calli M. Cain -- Impact of incarceration on families and communities / Nancy Rodriguez and Jillian J. Turanovic -- The two cultures / Alison Liebling and Deborah Kant -- Measuring and explaining inmate misconduct / Benjamin Steiner -- Prison riots / Bert Useem -- Drugs and prisons / Michael Wheatley, John R. Weekes, Andrea E. Moser, and Kathleen Thibault -- A general model of harm in correctional settings / Nancy Wolff -- Understanding the contours of prison disciplinary procedures / James Marquart and Chad Trulson -- The effects of administrative segregation / Paul Gendreau and Ryan M. Labrecque -- A comparison of British and American policies for managing dangerous prisoners / Roy D. King -- Adult offender assessment and classification in custodial settings / James Bonta and J. S. Wormith -- Principles of effective intervention with incarcerated offenders / Claire Goggin -- Employment and vocation programs in prison / Paula Smith, Lindsey M. Mueller, and Ryan Labrecque -- Treating sex offenders in prison / Devon L. L. Polaschek and Kristina M. Blackwood -- The multiple faces of reentry / Susan Turner -- Implementing prison-based treatment / James McGuire -- Preventing suicide in detention and correctional facilities / Robert D. Canning and Joel A. Dvoskin -- Offenders with mental illness in prison / Sarah M. Manchak and Robert D. Morgan -- The problem of incarcerating juveniles with adults / Jodi Lane and Lonn Lanza-Kaduce -- The effect of prisons on crime / Sarah Tahamont and Aaron Chalfin -- Private prisons in a new environment / Scott D. Camp and Kevin N. Wright -- Policy and program innovations in prisons / Faye S. Taxman and Brandy Blasko -- Current policies, future directions, and the goals of confinement / John Wooldredge